Shifting Paradigms in Translanguaging: A Scientometric Analysis of Research Trends and Trajectories - Lalu Nurul Yaqin; James Mclellan; Najib Noorashid (Universitas Syiah Kuala, 2025)
Over the past decade, numerous papers have documented translanguaging studies, significantly contributing to the shifting paradigm in this research area. Nevertheless, no comprehensive bibliometric analysis has been conducted on the landscape of translanguaging research to uncover the prominent areas and potential future directions. This study focuses on articles from the Scopus database published from 2014 to 2023 with the search keyword